A260 OUTCOMES OF LIVER TRANSPLANTATION FOR ACUTE LIVER FAILURE AMONG RECIPIENTS WITH ABO-IDENTICAL VS. ABO-COMPATIBLE VS ABO-INCOMPATIBLE GRAFTS. (1st March 2018) - Bahreini, Z
Abstract: Background: Acute liver failure is associated with a high mortality rate due to multi-organ failure, sepsis and cerebral edema. Liver transplantation remains the only life saving treatment available for these critically ill patients. Urgent liver transplantation within 48 to 72 hours has shown to be crucial for reducing the waiting list mortality of these patients. However, liver grafts are a scarce resource, leading to a significant rate of mortality for patients in need of urgent liver transplant. ABO-incompatible (ABO-in) liver transplantation is occasionally used as a rescue alternative when an ABO-identical (ABO-id) or compatible (ABO-c) graft is not available. The outcomes of ABO-in liver transplantation using deceased donors have been variable but mostly reported to be associated with poor graft function, early graft loss and an increased rate of complications. There are however limited studies examining long term outcomes of liver transplantation with ABO-in grafts. Aims: The aim of the study was to compare long term mortality and graft survival of patients undergoing liver transplantation with ABO-id vs. ABO-c and ABO-in donor grafts. A secondary objective was to determine other predictors of poor outcome in patients requiring urgent liver transplantation for acute liver failure. Methods: A retrospective cohort study was done to examine adult patients who underwent urgent liver transplantation between 1985 and 2016 in London, Ontario. Patients were divided into three cohorts depending on their grafts' ABO compatibility: ABO-id, ABO-c and ABO-in. Transplant outcomes in the peri and post transplant period were collected for all three cohorts. Multivariate logistic regression was used to assess ABO-compatibility as a predictor of graft failure and patients' death. Results: 73 patients with emergency liver transplantation were studied. Of those, 9.6% received an ABO-in graft. Rate of retransplantation in ABO-id, ABO-c and ABO-in groups was 2.5%, 11.5% and 57%, respectively. The OR of graft failure in the ABO-in group was 13 times greater when compared to ABO-id (OR 13.3, p 0.02). There was no statistically significant difference in graft survival between ABO-c and ABO-id groups (OR 3.5, p 0.12). OR of death was not significantly different between the three groups. Age (OR 1.06, p0.04), need for inotropic support (OR 6.2, p0.02) and stroke (OR 15.2, p0.03) were more important predictors of death than ABO compatibility itself. Conclusions: ABO-in liver transplantation was associated with higher rates of graft failure and retransplantation however there was no significant difference in long term mortality in these patients. In select adult patients with acute liver failure in need of an emergency liver transplantation, ABO-in transplants should be viewed as an important lifesaving therapeutic option with comparable results in long term survival. Funding Agencies: None